THE EFFECTS OF CLINICAL PILATES EXERCISES IN PATIENTS WITH RHEUMATOID ARTHRITIS - Yentur, S. Baglan; Atas, N.; Ozturk, M. A.; Oskay, D. (Elsevier, 2020)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 03, 2020 -- ELECTR NETWORK